Multivariate Models to Forecast Portfolio Value at Risk: from the Dot- Com crisis to the global financial crisis - Gabriel, Vítor Manuel de Sousa (Review of Business Management, 2014)
This study analyzed market risk of an international investment portfolio by means of a new methodological proposal based on Value-at- Risk, using the covariance matrix of multivariate GARCH-type models and the extreme value theory to realize if an international diversification strategy minimizes market risk, and to determine if the VaR methodology adequately captures market risk, by applying Backtesting tests. To this end, we considered twelve international stock indexes, accounting for about 62% of the world stock market capitalization, and chose the period from the Dot-Com crisis to the current global financial crisis. Results show that the proposed methodology is a good alternative to accommodate the high market turbulence and can be considered as an adequate portfolio risk management instrument.